International Monetary Fund Annual Report 1958. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1958)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1958. The report highlights that at the beginning of 1957, the world economy was still dominated by boom conditions generated by an intense worldwide wave of private and public investment, which was reflected in a large demand for capital. Already in some countries, there were signs that a period of readjustment was not far off, but most of the payments problems that called for treatment during the first three quarters of the year had their origin in the inflationary methods.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet